Theoretical Study on Factors Influencing the Efficiency of D–π′–A′–π–A Isoindigo-Based Sensitizer for Dye-Sensitized Solar Cells - Sarinya Hadsadee (2020)
© 2019, The Minerals, Metals & Materials Society. Abstract: We investigated metal-free dyes based on isoindigo by performing density functional theory and Time-dependent density functional theory calculations to improve the efficiency of dye-sensitized solar cells. The D–π′–A′–π–A organic dyes (TIDP and TIDT) used triphenylamine as donor, thiophene as the π′-linker between the donor and auxiliary acceptor, and a phenyl or thiophene ring as the π-linker between the auxiliary acceptor and acceptor. TIDP and TIDT exhibit good charge-transfer properties. The TIDP-based device provides better device performance with a PCE of 4.11%. Calculated results reveal that the phenyl ring directly linking the auxiliary acceptor and acceptor causes a small tilt angle in the TiO2–adsorped dye, resulting in enhanced electron-injection rates, more efficient packing of adsorbed dye molecules, and slow charge recombination at the TiO2 surface. The performance of the TIDT-based device (η = 2.46%), arises from decreased electron-injection rates and fast charge recombination caused by the large dihedral angle of the adsorbed dye. This research identifies a potential π′-linker group and reveals the influence of the π-linker on photovoltaic performance in organic dyes. Graphic Abstract: The phenyl ring directly linking the auxiliary acceptor and acceptor causes a smaller tilt angle in the TiO2-absorbed dye compared to thiophene ring resulting in enhanced electron-injection rates with increasing short-circuit current density (Jsc) as well as slow charge recombination at the TiO2 surface with increasing open-circuit voltage (Voc).[Figure not available: see fulltext.]